Experimental investigation of the effects of different quaternary elements (Ti, V, Nb, Ga, and Hf) on the thermal and magnetic properties of CuAlNi shape memory alloy - Ozkul, Iskender; Karaduman, Oktay; Simsek, Telem; Simsek, Tuncay; Canbay, Canan Aksu; Ibrahim, Pshdar Ahmed; Arpa, Ipek A. K. (Springer Heidelberg, 2022)
To discover cheaper and functional species of shape memory alloys (SMAs) is one of the main objectives for interested researchers. In this work, five different alloys were produced by adding different quaternary alloying elements (Ti, Ga, V, Hf, and Nb) into the ternary CuAlNi-base (C-) alloy.The thermal and structural properties of the produced alloys were investigated. The phases of Al7Cu23Ni, AlNi, CuNi2Ti, Al80V20, AlNbNi2, Cu3Ga, and NiSHf were observed by X-ray powder diffraction (XRD) analyses after arc melting processes. The average crystallite sizes of the produced alloys were calculated as 17.1, 18.9, 19.4, 20.8, and 23.7 nm for CV, CNb, CHf, CTi, and CGa alloys, respectively. The highest lattice strain was found at about % 0.572 for CGa alloy. Measuring the magnetic properties of the produced alloys revealed the paramagnetic behavior of the alloys at room temperature.
Keywords: Martensitic-Transformation; Grain-Refinement; Mems Applications; Thin-Films; Behavior; Additions; Field; Zr